A escrita de uma criança autista em ambiente digital: uma discussão sobre os precursores da escrita - Silva, Soraya Gonçalves Celestino da (2022)
Autism is a neurodevelopmental disorder characterized by difficulties in social interaction, communication and repetitive and restricted behaviors, according to DSM (2013). The process of writing acquisition in these children is different when compared to other typical children. This finding drove us to this study in the field of autistic literacy in the digital environment. The multimodality of the digital field directed our gaze to deepen the discussion about the precursors of Vigotsky's writing (1998, 2000, 2007). In this sense, this Thesis had as main objective to understand the process of acquiring the writing of an autistic child in a digital environment, from the precursors of Vigotsky's writing (1998, 2000, 2007). For the theoretical basis, the historical contextualization of autism brought the authors Kanner (1943), Rutter (1978), Assumpção Jr. et. Al. (1999) and Lopes (2000) until the diagnoses presented in the DSM; for the didactic sequence, support was in Dolz, Noverraz and Schneuwly (2004); for the notion of writing acquisition, the dialogue was conducted with authors such as Abaurre (1991); Vigotsky (1998, 2000, 2007); Faria (2008) and Cavalcante (2008). We also had, as a basis, official texts such as The Rights of Learning (BRASIL, 2012) and BNCC (2018), among others. Methodologically, the research, based on the research methodology, is framed as a case study, which was developed from two didactic sequences, composed of four modules each, elaborated through the pedagogy of multiliteracies and applied in the Specialized Educational Care (SEC) of an autistic child, enrolled in elementary school early years of a public school in Olinda (PE). During the years 2018 and 2019, in the months of August to November, the didactic sequences containing activities, games, games and drawings appropriate to their specificities were applied. The sequences were performed in the SEC, in the school environment. The analyses of the data show us: first, that the gesture, the drawing and the game served as scaffolding for the entry of this child in writing, opening didactic perspectives for working with autistic children; second, that the use of multiliteracies contributed to the advancement of the writing skills of this student; third, that the process of mediation of the SEC teacher was very important for the development of writing skills. With this, we understand that the symbolic representation in make-believe and in drawing is a stage prior to writing, which contributes to the development of the writing process. The data analyzed point to the need for the school to incorporate a methodology based on the precursors of Vigotsky’S writing (1998, 2000, 2007) and the mediation process for a better scope of the development of children's writing skills.